Corporate governance and incentive contracts: historical evidence from a legal reform - Christian Bayer; Carsten Burhop (Max Planck Institute for Research on Collective Goods, 2008)
This paper proposes to exploit a reform in legal rules of corporate governance to identify contractual incentives from the correlation of executive pay and firm performance. In particular, we refer to a major shift in the legal and institutional environment, the reform of the German joint-stock companies act in 1884. We analyze a sample of executive pay for 46 firms for the years 1870 to 1911. In 1884, a law reform substantially enhanced corporate control, strengthened the monitoring incentives of shareholders, and reduced the discretionary power of executives in Germany. Pay-performance sensitivity decreased significantly after this reform. While executives received a bonus of about three to five per cent in profits before 1884, after the reform this parameter decreased to a profit share of about two per cent. At least the profit share that is eliminated by the reform must have been incentive pay before. This incentive mechanism was replaced by other elements of corporate governance.
Keywords: G30; J33; N23; 330; pay-performance sensitivity; natural experiment; legal reform; corporate governance; Corporate Governance; Führungskräfte; Leistungsorientierte Vergütung; Anreizvertrag; Aktienrecht; Reform; Geschichte; Wirtschaftspolitische Wirkungsanalyse; Unternehmensentwicklung; Deutschland (bis 1945)